Hedgehogs and Angiostrongylus cantonensis: Uncovering the Role of Atelerix albiventris in the Parasite Life Cycle - Šipková, Anna; Javorská, Kristýna; Anettová, Lucia; Pandian, Divakaran; Cibulka, Petr; Kačmaříková, Jana; Novotný, Ladislav; Modrý, David (Integrative zoology, 2025)
The ongoing invasion of the zoonotic parasite Angiostrongylus cantonensis threatens humans, other mammals, and birds. In Mallorca, neurological disorders associated with this parasite are increasingly reported in free-living Algerian hedgehogs, Atelerix algirus, raising public health concerns. Experimental infections in the related species Atelerix albiventris were conducted to investigate the role of hedgehogs in the life cycle of the parasite. Captive-born hedgehogs were orally inoculated with 200 and 2000 third-stage larvae and monitored for 50 days by behavioral observations, blood tests (hematology and biochemistry), histopathology, and qPCR analysis. Baermann's larvoscopy was used to examine feces starting from day 39 post-infection (DPI). Neuropathological symptoms were only observed in the high-dose group, with larvae detected in brain tissue at 5, 15, 23, and 44 DPI. In contrast, no clinical symptoms or larvae in tissues were found in the low-dose group. Parasite DNA was present in the organs of both groups, but neurological migration occurred exclusively in the high-dose group. Blood tests showed no specific patterns indicating infection. Hedgehogs are aberrant hosts of A. cantonensis, showing severe neuropathological symptoms at high infection levels (2000 third-stage larvae), while lower doses remain asymptomatic. The parasite cannot complete its life cycle in A. albiventris hedgehogs, which do not contribute to its ecological circulation. However, hedgehogs can serve as sentinels for the spread of A. cantonensis in newly invaded regions like Mallorca. Monitoring neurological disease in wildlife could provide valuable insights into the potential spread of this zoonotic parasite in temperate latitudes.
Keywords: hedgehogs; Mediterranean region; experimental infection; Angiostrongylus cantonensis